2014
DOI: 10.1016/s2214-109x(14)70025-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between economic growth and early childhood undernutrition: evidence from 121 Demographic and Health Surveys from 36 low-income and middle-income countries

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 18 publications
8
127
1
5
Order By: Relevance
“…While empirical evidence of the role of economic growth for child nutrition is mixed (Smith & Haddad, 2002;Heady, 2013;Vollmer et al, 2014), most cross-country studies suggest a negative relationship between growth and undernutrition. To control for possible effects of economic growth, we use per capita gross domestic product (GDP) expressed in 2005 international dollars (adjusted for purchasing power parity, PPP) from WDI (World Bank, 2014).…”
Section: (C) Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…While empirical evidence of the role of economic growth for child nutrition is mixed (Smith & Haddad, 2002;Heady, 2013;Vollmer et al, 2014), most cross-country studies suggest a negative relationship between growth and undernutrition. To control for possible effects of economic growth, we use per capita gross domestic product (GDP) expressed in 2005 international dollars (adjusted for purchasing power parity, PPP) from WDI (World Bank, 2014).…”
Section: (C) Control Variablesmentioning
confidence: 99%
“…Second, the availability of anthropometric data is much better for women than for men. Many surveys include measurements for women of child-bearing age, but not for other adults in the household (Vollmer et al, 2014). We use data from DHS (ICF International, 2013).…”
mentioning
confidence: 99%
“…Hal inilah menyebabkan ketidakmerataan pada masyarakat dan berdampak pada kesehatan kelompok rentan, salah satunya balita. 21 Terdapat lima faktor yang diperkirakan dapat menentukan prioritas dan kecukupan alokasi pembiayaan bidang kesehatan, yaitu jumlah penerimaan daerah yang berasal dari pemerintah pusat dan daerah yang tercantum dalam APBD, skala prioritas bidang kesehatan di mata para pimpinan daerah, 10,22 kemampuan dinas kesehatan dalam melakukan advocay, kemampuan dinas kesehatan untuk menyusun rencana anggaran yang baik, dan kemampuan dinas kesehatan menyajikan informasi alur pendanaan kesehatan daerah termasuk informasi sumber-sumber dana yang ada sampai bagaimana penggunaan dana tersebut terhadap pencapaian program-program kesehatan. 10,20,23 Sebuah studi yang menggunakan data 121 survei yang melibatkan 36 negara berpendapatan rendah dan berpendapatan menengah menyebutkan bahwa pertumbuhan makro-ekonomi memiliki hubungan yang lemah atau bahkan tidak ada dalam hal kaitannya dengan balita pendek (stunting), berat rendah (underweight) dan gizi buruk (wasting).…”
Section: Gambar 2 Distribusi Prevalensi Gizi Buruk Kabupaten/kota DIunclassified
“…Fakta yang ditemukan meliputi pendapatan yang meningkat belum dipastikan terdistribusi dengan merata, serta dimanfaatkan dengan memperbaiki status gizi maupun untuk membangun fasilitas publik yang terkait dengan peningkatan status gizi balita. 22 Pada kenyataannya, selain besaran dana kesehatan, persentasenya terhadap total pendapatan maupun total belanja, hal yang lebih penting adalah pemanfaatan dana dengan efisien dan efektif. Dana-dana kesehatan yang besar tidak secara otomatis dapat meningkatkan derajat kesehatan.…”
Section: Gambar 2 Distribusi Prevalensi Gizi Buruk Kabupaten/kota DIunclassified
“…Further interventions to ensure equitable distribution of the world's food resources and maximizing nutrition opportunities for all are required. 6 In this issue of the journal, we include a number of nutrition studies related to public health in our region. The review of the burden of disease in Vietnam by Nhung and colleagues found that 71% of the disease burden is caused by noncommunicable diseases, with nutrition as the most important risk factor.…”
mentioning
confidence: 99%